2020
DOI: 10.4081/aiua.2020.2.78
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and uro-oncology follow-up: A “virtual” multidisciplinary team strategy and patients’ satisfaction assessment

Abstract: COVID-19 pandemic strongly modified the organizations of our clinical practice. Strict containment measures have been adopted to limit the disease diffusion. In particular, hospital face-to-face post discharge and follow up visits have been reduced. Although cancelling or deferring appointments seems to be a pragmatic approach, this solution may have a devasting long-term impact on health medical care and on patients. In this context, telemedicine and remote consultations may have the potential to provide heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 2 publications
1
32
0
Order By: Relevance
“…Other studies have examined the satisfaction of individuals with teleconsultation during the COVID-19 pandemic. Many of these studies were conducted in developed countries [ 24 , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. To the best of our knowledge, there is just one study in Saudi Arabia [ 43 ] and one study in India [ 44 ], which may have a similar research setting as Iran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have examined the satisfaction of individuals with teleconsultation during the COVID-19 pandemic. Many of these studies were conducted in developed countries [ 24 , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. To the best of our knowledge, there is just one study in Saudi Arabia [ 43 ] and one study in India [ 44 ], which may have a similar research setting as Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Dobrusin’s study [ 36 ] also concluded that patients were incredibly satisfied with their telehealth appointments, with more than 80 % suggesting that they could engage in potential telehealth visits and the provider is able to answer their questions. In AmbrosIti's study [ 35 ], patients with genitourinary cancer who had weekly video-conference meetings through Zoom with healthcare professionals showed that most patients had a high level of satisfaction with their telehealth visits. In Gilbert's study [ 37 ], in the United Kingdom, virtual consultations (via telephone or video call) were described as a possible alternative to face-to-face consultations during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, COVID-19 pandemic represents an important challenge and learning opportunity for cancer centers, in the context of an extremely dynamic clinical and political situation which requires maximum flexibility to be appropriately faced. For example, telemedicine can represent an alternative for both multidisciplinary and follow-up visits, as suggested by the preliminary experience of Ambrosini et al (38).…”
Section: Discussionmentioning
confidence: 99%
“…Thanks, mostly, to the uncommonness of the case, our experience strengthens the importance of sharing therapeutic and diagnostic strategies in a Cancer MDT that involves pathologists, oncologists, radiologists and urologists. Moreover, we are experiencing a unique historical moment due to the COVID‐19 pandemic, so we strongly support the powerful methodology of MDT, also by exploiting telemedicine strategies if face‐to‐face meetings are not feasible (Ambrosini et al., 2020).…”
Section: Discussionmentioning
confidence: 87%